Participative Management Style and its Relation to Employee Willingness to Accept Job Offer in the Same Company Once Again - Rolkova, Monika (Communications - Scientific letters of the University of Zilina, 2013)
Participative management style is based on the involvement of employees in decision-making and problem-solving in the company, as well as on supporting their high autonomy and own initiative. The article describes outcomes of the research which examines the interaction between the management style and willingness of employees to accept job offer in the current company once again if they were asked in the future. Results confirmed that there is highly significant correlation between the belief of employees they would accept the job offer in the same enterprise again and their satisfaction with current management style as well as use of the elements of participative management style.